Laringectomizados usuários de prótese traqueoesofágica: princípios e métodos da prática fonoaudiológica - Ghirardi, Ana Carolina de Assis Moura (2007)
The aim of the present study is to analyze the principles and methods present in Speech Therapy of totally laryngectomized patients who use a tracheoesophageal prosthesis. Methods: The participants of the study were three speech therapists with experience in the field of laryngectomy rehabilitation, three head and neck surgeons and three patients using a vocal prosthesis for a minimum period of one year. The subjects were divided into three separate groups, according to their role in the study: Speech therapists (GF), head and neck surgeons (GM) and patients (GU). The speech therapists were submitted to an open interview, in which they assessed their clinical practice with such patients, in detailed manner. After reading the material collected from these interviews, a questionnaire was developed so that the surgeons could consider their expectations towards speech therapy as well as their ideas on clinical success. Likewise, a third questionnaire was developed, targeting the patients views on speech therapy, their recollections on the subject and their references to specific clinical strategies. After all interviews and questionnaires were collected, the material was thoroughly read several times, and the content was organized in different categories which derived from the contents of subjects speech. Speech order was maintained while organizing the categories. Thus, the data analysis was done considering each group separately, since not all categories were the same for the three groups. However, a comparison was made for all groups, with regards to those categories that matched in all three. Results: The time span of therapy was considered small by GF. The most common techniques described by the speech therapists were those aiming stoma occlusion, coordination between occlusion, breathing and speech, speech intelligibility and pitch and loudness modulations. For this group, the main objective of speech therapy is to ensure that the vocal prosthesis is the main way of alaryngeal communication, if the patient so desires. For GM, the main role of speech therapy is to provide vocal expression resources so that the patient can achieve communicative independence. They also feel that speech therapy should be a space where the patients learn to master their prosthesis resources and learn how to care for it effectively. As for GU, the main gain related to speech therapy was improvement in quality of life, due to the re-gaining of speech and voice, leading to greater social interaction. All viewed their time with the speech therapist as a positive one, and do not necessarily consider a short time-span as a main advantage of the tracheoesophageal prosthesis. As a result of the combined analysis, the principles of speech therapy with these patients are: to insure the patients adjustment to their prosthesis, to present them with specific speech techniques and to promote conditions where the patient is free to express himself and thus expand the abilities acquired in therapy to his daily life activities. Conclusions: Therefore, the main goal of speech therapy is a combination of the aspects pointed out by members of the three groups; that is, to provide the patient with independence to handle and use his prosthesis not only in a daily manner, but with mastery of all its resources and expression possibilities, but to promote as well a greater social interaction of these people with their peers, hence improving their overall quality of life